Field research 2014 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2014)
The research program at the East Central Kansas Experiment Field is designed to keep area crop producers abreast of technological advances in agronomic agriculture. Specific objectives are to (1) identify top performing varieties and hybrids of wheat, corn, soybean, and grain sorghum; (2) establish the amount of tillage and crop residue cover needed for optimum crop production; (3) evaluate weed and disease control practices using chemical, no chemical, and combination methods; and (4) test fertilizer rates, timing, and application methods for agronomic proficiency and environmental stewardship. Contributors: E.A. Adee, Assistant Professor, Kansas River Valley Experiment Field, Topeka I. Campitti, Assistant Professor, Dept. of Agronomy, K-State, Manhattan G. Cramer, Assistant Professor, South Central Experiment Field, Hutchinson E. DeWolf, Professor, Dept. of Plant Pathology, K-State, Manhattan B.J. Haverkamp, Graduate Student, Dept. of Agronomy, K-State, Manhattan J.D. Jennnings, Graduate Research Assistant, Dept. of Agronomy, K-State, Manhattan J. Kimball, Plant Science Tech, East Central Experiment Field, Ottawa K. Kusel, Research Assistant, Southeast Agricultural Research Center, Parsons C.R. Little, Associate Professor, Dept. of Plant Pathology, K-State, Manhattan C. Minihan, Assistant Scientist, Dept. of Agronomy, K-State, Manhattan S. Naeve, Associate Professor, Agronomy and Plant Genetics, University of Minnesota D.E. Peterson, Professor, Dept. of Agronomy, K-State, Manhattan P.V.V. Prasad, Professor, Crop Physiology, Dept. of Agronomy, K-State, Manhattan D. Presley, Associate Professor, Dept. of Agronomy, K-State, Manhattan C.B. Rajashekar, Professor, Dept. of Horticulture, Forestry, and Recreation Resources, K-State, Manhattan K.L. Roozeboom, Associate Professor, Cropping Systems, Dept. of Agronomy, K-State, Manhattan G. Sassenrath, Associate Professor, Southeast Agricultural Research Center, Parsons A. Schlegel, Professor, Southwest Research-Extension Center, Garden City D. Shoup, Extension Specialist, Crops and Soils, Southeast Area Office, Chanute J. Shroyer, Extension Specialist, Agronomy, K-State, Manhattan C.R. Thompson, Professor, Dept. of Agronomy, K-State, Manhattan E. Wilson, Graduate Student, Agronomy and Plant Genetics, University of Minnesota
Keywords: Kansas Agricultural Experiment Station contribution; no. 14-352-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1102; Kansas; Alfalfa; Corn; Grain sorghum; Soybeans; Wheat; Crops